the The Effect of Small-Sided Games Training on the Passing Accuracy of Futsal Players at State Senior High School 2 Palopo : An Experimental Study at state senior high School 2 Palopo - agung, Astheonar setia; jalil, Rasyidah (UNIB Press, 2025)
This study aimed to determine the effect of small-sided games (SSG) training on improving the passing accuracy of futsal players at State Senior High School 2 Palopo. The research employed an experimental method using a one-group pretest-posttest design. The sample consisted of 12 futsal players selected through a total sampling technique. Data were collected using a passing accuracy test administered before and after the training intervention. The results indicated a significant improvement in passing accuracy following the SSG training program. A paired-sample t-test revealed a significance value (Sig.) of 0.000 < 0.05, demonstrating a significant difference between the pretest and posttest results. It can therefore be concluded that small-sided games training has a positive and significant effect on improving the passing accuracy of futsal players at State Senior High School 2 Palopo”